2018
DOI: 10.3390/pr7010009
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Reaction Selectivity Using CFD-Based Compartmental Modeling and Surrogate-Based Optimization

Abstract: Mixing is considered as a critical process parameter (CPP) during process development due to its significant influence on reaction selectivity and process safety. Nevertheless, mixing issues are difficult to identify and solve owing to their complexity and dependence on knowledge of kinetics and hydrodynamics. In this paper, we proposed an optimization methodology using Computational Fluid Dynamics (CFD) based compartmental modelling to improve mixing and reaction selectivity. More importantly, we have demonst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The CM may be successfully applied for the prediction of hydrodynamics in the analyzed systems [17,18]. The hybrid approach based on the combination of CFD and CM techniques is also discussed in the literature [19,20]. Hristov et al (2004) reported that the CFD-based compartmental model could be used to describe the performance of novel impeller geometry in a triple impeller bioreactor [21].…”
Section: Of 12mentioning
confidence: 99%
“…The CM may be successfully applied for the prediction of hydrodynamics in the analyzed systems [17,18]. The hybrid approach based on the combination of CFD and CM techniques is also discussed in the literature [19,20]. Hristov et al (2004) reported that the CFD-based compartmental model could be used to describe the performance of novel impeller geometry in a triple impeller bioreactor [21].…”
Section: Of 12mentioning
confidence: 99%
“…Surrogate models are common in applications where the original model does not easily lend itself to optimisation, e.g. Palmer and Realff (2002), Caballero and Grossmann (2008), Fahmi and Cremaschi (2012), Boukouvala et al (2017), Beykal et al (2018), Jones et al (2018), Carpio et al (2018) and Yang et al (2019). Common surrogate models include e.g.…”
Section: Design Of Experiments For Black-box Model Discriminationmentioning
confidence: 99%
“…Another work that investigated the improvement on the chemical reaction was reported by Yang et al [5], who proposed an optimisation methodology using Computational Fluid Dynamics (CFD) based compartmental modelling to improve mixing and reaction selectivity. Results demonstrate that reaction selectivity can be improved by controlling rates and feed locations of the reactor.…”
Section: Brief Synopsis Of Papers In the Special Issuementioning
confidence: 99%